Effect of Different Glass Modifiers on Structural, Optical and Mechanical Properties of Borosilicate Glasses - Gill, Kiranpreet Kaur (My University, 2011)
Glasses find applications in various fields like optics and optoelectronics. In the present work, the glasses are synthesized by melt quenching techniques. These glasses are characterized by various techniques such as X-ray diffraction, Fourier-Transform-Infrared spectroscopy (FT-IR), U.V. Visible spectroscopy to study the effect of replacement of various modifiers in the glass like BaO by CaO, MgO and SrO. The results are discussed in light of non-bridging oxygen (NBO), optical basicity etc. The micro-hardness and variation of refractive index with wavelength is also considered. All the work is done with pristine glasses i.e. non heat-treated glasses.
M.Sc. (SPMS)
Keywords: Borosilicates; Optical; Mechanical; Microhardness